Ramadan Mubarak - "Khan, Saniyasnain" (China; Goodword Book, 2024)
During Ramadan, the doors of Paradise are open, inviting us to grow closer to Allah through fasting, prayer, and reading the Quran. Fasting during this holy month teaches patience and self-discipline, helping us develop stronger character. Ramadan also encourages compassion and sympathy, as we become more aware of the needs of others. It is a special time to focus on doing good deeds and cultivating positive habits that last beyond the month. Finally, the month concludes with the joyous celebration of Eid ul-Fitr, marked by a big feast shared with family and friends.
Keywords: Islamic Value